Penguatan Pembelajaran PAI Berbasis Deep Learning Meningkatkan Literasi Keagamaan Di Era Digital - Mu’allimah Rodhiyana; Sutiono AZ; Ita Rosita; Ridma Diana; Ahmad Mustaghfirin (SAP (Susunan Artikel Pendidikan), 2025)
This study aims to analyze the effectiveness of deep learning-based Islamic Religious Education (PAI) in improving religious literacy in the digital era. The deep learning approach focuses not only on the depth of the material but also on the meaningfulness of the mindful, joyful, and meaningful learning process. This study employed library research, reviewing various relevant sources. Data were analyzed using content analysis techniques through the stages of reduction, presentation, and conclusion drawing. The results show that mindful learning strengthens students' awareness of religious values; joyful learning creates a pleasant learning environment that encourages motivation and active engagement; while meaningful learning makes PAI material relevant to the realities of everyday life, including digital challenges. This approach has been proven to align with the goals of Islamic education, which emphasize the integration of knowledge and morals, and aligns with the independent curriculum policy, which focuses on character building and student-centered learning. In conclusion, deep learning-based PAI reinforcement can be a pedagogical and preventive strategy in dealing with the rapid flow of digital information. This model has the potential to develop a generation of Muslims who are literate, critical, moderate, and virtuous. These findings are expected to provide conceptual and practical contributions for teachers, curriculum developers, and Islamic education researchers in the future.